1979
DOI: 10.1002/cpt1979266718
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir kinetics after intravenous infusion

Abstract: The disposition and safety of the antiviral drug acyclovir were studied in 14 subjects with advanced malignancies. Acyclovir was administered by a 1-hr intravenous infusion at doses of 0.5, 1.0,2.5, and 5.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 10 publications
(10 reference statements)
2
34
0
Order By: Relevance
“…The only significant metabolite of acyclovir which has been isolated to date is 9-carboxymethoxymethylguanine (4, 5), which accounts for less than 14% of the administered dose. The renal clearance of acyclovir after a single 1-h infusion is two-to threefold greater than the creatinine clearance (4,5,7,13). This suggests that acyclovir is eliminated by other renal mechanisms in addition to glomerular filtration and that renal tubular secretion may play an important role in acyclovir elimination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The only significant metabolite of acyclovir which has been isolated to date is 9-carboxymethoxymethylguanine (4, 5), which accounts for less than 14% of the administered dose. The renal clearance of acyclovir after a single 1-h infusion is two-to threefold greater than the creatinine clearance (4,5,7,13). This suggests that acyclovir is eliminated by other renal mechanisms in addition to glomerular filtration and that renal tubular secretion may play an important role in acyclovir elimination.…”
mentioning
confidence: 99%
“…Although statistically significant, these effects due to the influence of probenecid probably have only limited clinical importance. In this study we confirmed that acyclovir is eliminated predominantly by renal clearance, both by glomerular filtration and tubular secretion; our results suggested that at least part of the tubular secretion is inhibited by probenecid.Acyclovir, a potent anti-herpesvirus agent, is eliminated predominantly by renal excretion (2,4,5,7,13). The only significant metabolite of acyclovir which has been isolated to date is 9-carboxymethoxymethylguanine (4, 5), which accounts for less than 14% of the administered dose.…”
mentioning
confidence: 99%
“…This antiherpetic agent has demonstrated low toxicity, good metabolic stability, and broad tissue distribution in preclinical trials (9,24). Therefore, acyclovir can be considered an antiviral agent with great therapeutic potential in humans.…”
mentioning
confidence: 99%
“…Among 23 human patients who were treated with ACV intravenously at a dose of 5 mg/kg three times a day for 5 days, the only toxicity observed was a reversible increase in blood urea nitrogen in 2 (28). In another study (9) there was no indication of toxicity either clinically or from laboratory observations in any of the human subjects after a 1-h intravenous infusion of ACV at doses of up to 5 mg/kg. In our study, no gross or microscopic lesions were observed that could be attributed to drug toxicity after we had given newborn rabbits 6 or 12 daily intraperitoneal injections of the drug that amounted to 50 mg/kg of body weight per day.…”
Section: Methodsmentioning
confidence: 91%
“…Toxicity, rapid metabolic breakdown, or insolubility of these compounds further limited their therapeutic use. Acyclovir (ACV) [9-(2-hydroxyethoxymethyl)-guanine], formerly known as "acycloguanosine," is an attractive candidate for treatment of neonatal HSV infections, since it has a high level of activity against HSV infections both in vitro (10) and in vivo (17,28) with minimal toxicity in vivo (9,28,29). This paper reports the results on a study on the efficacy of ACV against HSV type 2 (HSV-2) skin infections in newborn rabbits, an experimental model described previously (20).…”
mentioning
confidence: 99%